Cephalosporin-3G, Highly Prescribed Antibiotic to Outpatients in Rajshahi, Bangladesh: Prescription Errors, Carelessness, Irrational Uses are the Triggering Causes of Antibiotic Resistance - Aktar Uzzaman Chouduri, Mohitosh Biswas, Md. Uzzal Haque, Md. Saiful Islam Arman, Najem Uddin, Nurunnahar Kona, Reshma Akter, Anwarul Haque (Journal of Applied Pharmaceutical Science, 2018)
The study aims to assess the prescribing practices of antibiotics to outpatients attending public-private hospitals in Bangladesh and to investigate how the irrational uses of antibiotics influence the development of antimicrobial resistance in pathogens over time. A cross-sectional survey was conducted on 1100 prescriptions by interviewing outpatients at the exit point and at retail pharmacies. Infections in male patients (67%) were greater than female (32%). Unexpectedly 22% of patients visited quack doctors (unauthorized doctors), 32% did not complete antibiotic courses, and 10% took multiple antibiotics. As prescription errors the directions for antibiotic use were incomplete in 40% of cases and in a few cases, dosage form information was incomplete (17%) and absent (5%). The disease recovery rate was 12%, although no diagnostic test was performed in the majority (73%) of cases and no comments about disease recovery were in 81% cases. Post-operative infection was commonly found which could preferably be treated with rarely used antibiotics of DNA- or protein-synthesis inhibitors. Rarely used antibiotics (0.18–2% of prescribed antibiotics) were 1GCs, amoxicillin, co-amoxiclav, gatifloxacin, pefloxacin, and sparfloxacin. Most frequently prescribed antibiotics were cephalosporins (34%) followed by quinolones (16%), metronidazole (15%), macrolides (13%) and penicillins (7%). 3GCs (ceftriaxone, cefixime, ceftazidime), ciprofloxacin, azithromycin, and flucloxacillin were highly prescribed drugs in their respective groups. For better treatment, appropriate knowledge and practices regarding rational use of antibiotics need to be improved in patients and physician’s level. Simultaneously drug authority should exercise power to control the misuse of antibiotics.
Keywords: Outpatients, antibiotic use,knowledge, awareness,Bangladesh.